Synthesis, characterization, Hirshfeld surface, cytotoxicity, DNA damage and cell cycle arrest studies of N, N-diphenyl-N `-(biphenyl-4-carbonyl/4-chlorobenzoyl) thiocarbamides - Pandey, Sunil K.; Pratap, Seema; Rai, Sunil K.; Marverti, Gaetano; Kaur, Manpreet; Jasinski, Jerry P. (Journal of Molecular Structure, 2019)
The condensation reaction of biphenyl-4-carbonyl isothiocyanate/4-chlorobenzoyl isothiocyanate with diphenylamine yielded two new compounds; N-diphenyl-N'-(biphenyl-4-carbonyl) thiocarbamide (1) and N, N-diphenyl-N'-(4-chlorobenzoyl) thiocarbamide (2). Structure of the compounds were determined by analytical, spectroscopic (UV-Visible, FT-IR, H-1, & C-13 NMR), powder and single-crystal X-ray diffraction methods. Hirshfeld surface analysis and their associated two dimensional fingerprint plots of compounds were used as theoretical approach to assess driving force for crystal structure formation via the intermolecular interactions in their crystal lattices. The compounds were screened for their in vitro cytotoxicity activity against a panel of five human cancer cell lines namely; cervical (2008 and C13*) and ovarian carcinoma (A2780, A2780/CP and IGROV-1). Both the compounds exhibited promising activity against cervical and IGROV-1 cancer cells whereas for the other two cell lines appreciable activities were observed. The cell cycle arrest at G(0)/G(1) phase is supported by the DNA damage and apoptosis studies of the compounds against 2008, C13* and IGROV-1 cell lines. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: DNA damage and cell cycle arrest; Hirshfeld surface analysis; In vitro cytotoxicity; Thiocarbamide; X-ray crystal structure

Structural, Hirshfeld surface and in vitro cytotoxicity evaluation of five new N-aryl-N'-alkoxycarbonyl thiocarbamide derivatives - Pandey, Sunil K.; Pratap, Seema; Rai, Sunil K.; Marverti, Gaetano (Phosphorus Sulfur and Silicon and the Related Elements, 2020)
Five new compounds, N-(2, 4-dichlorophenyl)-N'-(methoxycarbonyl) thiocarbamide (1), N-(2, 4-dichlorophenyl)-N'-(ethoxycarbonyl) thiocarbamide (2), N-(2, 4-dichlorophenyl)-N'-(2, 2, 2-trichloroethoxycarbonyl) thiocarbamide (3), N-(2,4-dichlrophenyl)-N'-(pentoxycarbonyl) thiocarbamide (4) and N-(4-nitrophenyl)-N'-(pentoxycarbonyl) thiocarbamide (5), have been synthesized by the reaction of various alkoxy chloroformates with 2, 4-dichloroaniline/4-nitroaniline.The molecular structures of the compounds were elucidated by using spectroscopic methods (FT-IR, H-1 and C-13 NMR) and single-crystal X-ray structure analysis of compounds 2 and 5. Antiperiplanar orientation of C = O and C = S group across C-N bonds of thiocarbamide core may be due to the presence of intramolecular (N-H center dot center dot center dot O-C) hydrogen bond in the crystal structure of both the compounds. The presence of intermolecular interactions (C-H center dot center dot center dot S, C-H center dot center dot center dot O and N-H center dot center dot center dot S) in the molecular structure of the compounds has been studied in detail using Hirshfeld surfaces and their associated twodimensional fingerprint plots. In vitro cytotoxicity screening of the synthesized compounds evaluated on a panel of seven human cancer cell lines (cervical carcinoma (2008, C13*), colorectal (HT29 and HCT116) and ovarian carcinoma (A2780, A2780/CP and IGROV-1)) demonstrated significant inhibitory properties.
Keywords: Hirshfeld surface analysis; In vitro cytotoxicity; Thiocarbamide; X-ray crystal structure determination

Synthesis, characterisation, Hirshfeld surface and in vitro cytotoxicity evaluation of new N-aryl-N `-Alkoxycarbonyl thiocarbamide derivatives - Pandey, Sunil K.; Pratap, Seema; Rai, Sunil K.; Marverti, Gaetano; Kaur, Manpreet; Jasinski, Jerry P. (Journal of Molecular Structure, 2020)
Four new compounds N-(4-nitrophenyl)-N'-(isobutoxycarbonyl) thiocarbamide (1), N-(2, 4-nitrophenyl)-N'-(isobutoxycarbonyl) thiocarbamide (2), N-(4-nitrophenyl)-N'-(ethoxycarbonyl) thiocarbamide (3) and N-(2-Chloro- 4-nitrophenyl)-N'-(ethoxycarbonyl) thiocarbamide (4) were prepared and their structures confirmed by using various spectroscopic (FT-IR, UV-Visible, H-1 and C-13 NMR) and single crystal X-ray studies of 1 and 3. The presence of intramolecular (N-H center dot center dot center dot O=C) hydrogen bond in the crystal structure of both the compounds causes planarity of carbonyl thiocarbamide unit and trans orientation of C=O and C=S group. The intermolecular contacts (C-H center dot center dot center dot S, C-H center dot center dot center dot O and N-H center dot center dot center dot S) present in crystal structures have been examined by Hirshfeld surface analysis and their associated 2D fingerprint plots. All the compounds were assessed for their in vitro cytotoxic properties against a panel of seven human cancer cells such as cervical carcinoma (2008, C13*), colorectal (HT29 and HCT116) and ovarian carcinoma (A2780, A2780/CP and IGROV-1). Among them, compounds 2 and 4 exhibited better activity than 1 and 3 against all the cell lines tested. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Hirshfeld surface analysis; In vitro cytotoxicity; Thiocarbamide; X-ray crystal structure

Dabrafenib-panobinostat salt: improving the dissolution rate and inhibition of BRAF melanoma cells - Rai, Sunil K.; Marverti, Gaetano; Gunnam, Anilkumar; Allu, Suryanarayana; Nangia, Ashwini K. (ACS Omega, 2023)
Cocrystallization of the drug-drug salt-cocrystal of the histone deacetylase inhibitor (HDACi) panobinostat (PAN) and b-rapidly accelerated fibrosarcoma (BRAF) inhibitor dabrafenib (DBF) afforded single crystals of a two-drug salt stabilized by N+-H center dot center dot center dot O and N+-H center dot center dot center dot N- hydrogen bonds between the ionized panobinostat ammonium donor and dabrafenib sulfonamide anion acceptor in a 12-member ring motif. A faster dissolution rate for both drugs was achieved through the salt combination compared to the individual drugs in an aqueous acidic medium. The dissolution rate exhibited a peak concentration (Cmax) of approximately 310 mg cm-2 min-1 for PAN and 240 mg cm-2 min-1 for DBF at a Tmax of less than 20 min under gastric pH 1.2 (0.1 N HCl) compared to the pure drug dissolution values of 10 and 80 mg cm-2 min-1, respectively. The novel and fast-dissolving salt DBF-center dot PAN+ was analyzed in BRAFV600E melanoma cells Sk-Mel28. DBF-center dot PAN+ reduced the dose-response from micromolar to nanomolar concentrations and lowered IC50 (21.9 +/- 7.2 nM) by half compared to PAN alone (45.3 +/- 12.0 nM). The enhanced dissolution and lower survival rate of melanoma cells show the potential of novel DBF-center dot PAN+ salt in clinical evaluation.